Immigrants, family strategies and long-term settlement: the lessons of the crisis in rural areas - Sampedro Gallego, Rosario; Camarero Rioja, Luis (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2017)
The settlement of foreign born immigrants in Spanish rural areas in the last decades has been considered like an opportunity to stop depopulation and improve social and economic life in rural towns and villages. After the burst out of economic crisis in 2008 a lot of questions arise about factors that enhance or hinder the permanence of these newcomers in rural areas. In this paper we analyze the evolution of foreign born population in Castilla y Leon from 2007 to 2014, using data from Spanish Register of Inhabitants and from the Spanish Population Census of 2011. We relate the observed evolution of five national groups of immigrants with their family migration strategies and labour patterns. Data suggest that certain family migration strategies —those linked to transnational families and to marriage with Spaniards— and certain labour patterns —with a clear gendered pattern of employment— are connected with the permanence of immigrants in rural areas.
Keywords: Immigration; rural areas; family strategies; employment; Castilla y León.